DAMPAK NEGATIF PENGIRIMAN TKI KE LUAR NEGERI TERHADAP KEHIDUPAN KAUM PEREMPUAN SASAK (Studi Kasus di Pulau Lombok Provinsi NTB) - Ahmad Fauzan (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2021)
Abstract-The purpose of this study is (1) How to compare the quantity of the quality of the positive an d negative impact as a result of sending TKI abroad (2) What are the factors that contribute to the emergence of negative impacts of sending TKI (3) What are the efforts taken to overcome and reduce the negative impact of sending TKI.The result of the study indicate that the positive impact of development of Indonesia Migrant Workers to the national health is greater than the nagitve impact. The positive impact is improving the family’s economy, being able to bulid houses., buying rice fields and helping poor families. Meanwhile, the negative impact on the sending migrant workers is slow remittances. Vulnerable to the occurrence of misappropriation of wives with other man because no one is determined to leave her husband, kawm with other people.